2016
DOI: 10.1038/srep28071
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the EGFR pathway in Metazoa and its diversification in the planarian Schmidtea mediterranea

Abstract: The EGFR pathway is an essential signaling system in animals, whose core components are the epidermal growth factors (EGF ligands) and their trans-membrane tyrosine kinase receptors (EGFRs). Despite extensive knowledge in classical model organisms, little is known of the composition and function of the EGFR pathway in most animal lineages. Here, we have performed an extensive search for the presence of EGFRs and EGF ligands in representative species of most major animal clades, with special focus on the planar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 61 publications
(109 reference statements)
2
30
0
Order By: Relevance
“…These results strongly suggest that Smed-egfr-1 is not required for the specification of gut progenitors but is required for their differentiation into mature phagocytes and goblet cells (Barberán et al, 2016a). In this same study, the authors identified a putative ligand of Smed-egfr-1 named Smed-nrg-1, which shares homology with neuregulin-type EGF ligands (Barberán et al, 2016b). The silencing of Smed-nrg-1 phenocopies the defects observed after knockdown of Smed-egfr-1, supporting the hypothesis that Smed-nrg-1 may act as a ligand of Smed-egfr-1 in vivo, thereby regulating the differentiation of gut progenitors.…”
Section: Gut Cellsmentioning
confidence: 94%
See 1 more Smart Citation
“…These results strongly suggest that Smed-egfr-1 is not required for the specification of gut progenitors but is required for their differentiation into mature phagocytes and goblet cells (Barberán et al, 2016a). In this same study, the authors identified a putative ligand of Smed-egfr-1 named Smed-nrg-1, which shares homology with neuregulin-type EGF ligands (Barberán et al, 2016b). The silencing of Smed-nrg-1 phenocopies the defects observed after knockdown of Smed-egfr-1, supporting the hypothesis that Smed-nrg-1 may act as a ligand of Smed-egfr-1 in vivo, thereby regulating the differentiation of gut progenitors.…”
Section: Gut Cellsmentioning
confidence: 94%
“…A recent study demonstrated a key role of the epidermal growth factor receptor (EGFR) signaling pathway in the differentiation of gut progenitors during regeneration and homeostasis (Barberán et al, 2016a). Smed-egfr-1 is one of several planarian homologues of the EGFR family of tyrosine kinase receptors (Barberán et al, 2016b) and is expressed in differentiated gut cells and in gut progenitors in the mesenchyme around the gut branches (Barberán et al, 2016a). Whereas Smed-egfr-1 silencing inhibits the differentiation of new gut cells, as demonstrated in EdU incorporation experiments, the number of gut progenitors defined by co-expression of hnf-4/SMEDWI-1 and gata4/5/6/SMEDWI-1 increases significantly.…”
Section: Gut Cellsmentioning
confidence: 99%
“…Nevertheless, some potential factors or downstream effectors have been identified from RNAi screens. The epidermal growth factor receptor (EGFR) signaling pathway is crucial for neoblast regulation and cell fate specification . Smed‐egfr‐3 RNAi inhibits blastema formation and impairs cellular differentiation because of a dysregulation in asymmetric cell division .…”
Section: Molecular Mechanisms Underlying Nervous System Regenerationmentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR) signaling pathway is crucial for neoblast regulation and cell fate specification. [101][102][103] Smed-egfr-3 RNAi inhibits blastema formation and impairs cellular differentiation because of a dysregulation in asymmetric cell division. 101,103 Smed-egr-4, a putative downstream target of Smed-egfr-3, is primarily expressed in the brain and is required for brain regeneration; when Smed-egr-4 is knocked down, planarians reestablish anterior polarity, but fail to induce neural specification or form a brain primordium.…”
Section: Signaling Factors Involved In Brain Inductionmentioning
confidence: 99%
“…Therefore, Smed--egfr--1 appears to be necessary not for the specification of the gut progenitors but for their final differentiation (Barberán et al, 2016a). In planarians, the EGFR family has been expanded and 6 homologues have been identified in the model species Schmidtea mediterranea (Barberán et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%